2014
DOI: 10.5897/jabsd2014.0224
|View full text |Cite
|
Sign up to set email alerts
|

Production, consumption and nutritional value of cassava (Manihot esculenta, Crantz) in Mozambique: An overview

Abstract: Both soils and climate in Mozambique suit cassava cultivation and nine million tons fresh weight is produced annually, with a consumption of 85 kg per person per year. The roots are a staple carbohydrate and cooked leaves are served as a vegetable. Cassava is essential to food security, as it is a subsistence crop. Roots and leaves contain vitamin C and some minerals but are deficient in proteins and amino-acids. Although cassava is cultivated by about 63% of the population, cyanogenic glycosides and other ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 46 publications
6
51
0
6
Order By: Relevance
“…The cyanogenic potential of known cassava cultivars ranges from 10 mg HCN/kg to more than 500 mg HCN/kg [26]. The bitter varieties have been reported to contain higher concentrations of HCN, whereas the sweet varieties contain lower levels of HCN [23]. The use of cassava as food and feed for human and animals is greatly compromised by its level of HCN.…”
Section: Anti-nutritional Factors In Cassava Rootmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyanogenic potential of known cassava cultivars ranges from 10 mg HCN/kg to more than 500 mg HCN/kg [26]. The bitter varieties have been reported to contain higher concentrations of HCN, whereas the sweet varieties contain lower levels of HCN [23]. The use of cassava as food and feed for human and animals is greatly compromised by its level of HCN.…”
Section: Anti-nutritional Factors In Cassava Rootmentioning
confidence: 99%
“…Again, because cassava root meal is deficient in carotene and other carotenoids, one of the ways to overcome this deficiency is to supplement cassava root meal with cassava leaf meal with its high carotene and protein, hence combining a high-energy/low protein and high protein/low energy ingredients to meet the nutritional requirement of birds. In a study where maize was replaced with diets containing varying levels of cassava root meal and cassava leaf meal mixture showed that feed intake was improved, mortality was low and feed cost per weight gain was least when broilers were fed up to 75% of such mixture in the diet [23]. Due to dustiness, researchers have supplemented cassava meal-based diets with oil to reduce this limitation; while in some cases, palm oil supplementation is used to balance energy in the diet.…”
Section: Miscellaneous Supplementsmentioning
confidence: 99%
“…Alcoholic fermentation is not exclusive to S. cerevisiae [19,26,47]. An important attribute of a brewer's yeast-an ability to ferment simples sugars, even in the absence or presence of excess O 2 [80], is present in non-conventional yeasts.…”
Section: Yeastsmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends ferrous sulfate, ferrous fumarate and sodium iron EDTA (NaFeEDTA) for the fortification of wheat and maize [11]. Iron fortification of cassava mahewu could alleviate dietary iron deficiency anaemia in vulnerable populations such as women of child-bearing age and young children in Mozambique [8]. Fortification of cassava mahewu has been further supported by a report maintaining that populations consuming cassava as their basic energy source are at risk of deficient iron intake [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cassava roots are consumed in various forms: stiff porridge (karakata); roasted cassava or rale [6]; bread and other baked products [7]; cooked with vegetables and peanuts (xiguinha) and the non-alcoholic fermented traditional beverage mahewu [8]. Cassava mahewu is made from the roots of both bitter and sweet varieties and it is often sweetened with sugar just before consumption.…”
Section: Introductionmentioning
confidence: 99%